1959
DOI: 10.1111/j.1365-2621.1959.tb17301.x
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL CHANGES ASSOCIATED WITH THE RIPENING OF APPLES AND TOMATOESa

Abstract: The ripening and eventual softening of fruits is a natural phenomenon. More knowledge concerning the chemical changes associated with ripening is necessary to improve the present handling techniques for maintaining the quality of fruits in fresh market channels. In this study, the chemical changes of several constituents in whole apples and tomatoes were ascertained at the unripe, ripe, and overripe stages of maturity to help explain the softening process.Objective measurements of fruit quality have as their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1962
1962
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is interesting too that the degree of esterification is higher in the latter case. Doesburg (1959b) and Woodmansee et al (1959) recently reported that, contrary to previously published observations, neither the degree of polymerization nor the degree of esterification of apple pectins changes materially during ripening and storage.…”
Section: Effect Of Acid Concentrationmentioning
confidence: 57%
See 1 more Smart Citation
“…It is interesting too that the degree of esterification is higher in the latter case. Doesburg (1959b) and Woodmansee et al (1959) recently reported that, contrary to previously published observations, neither the degree of polymerization nor the degree of esterification of apple pectins changes materially during ripening and storage.…”
Section: Effect Of Acid Concentrationmentioning
confidence: 57%
“…This variety was selected because it was investigated fairly extensively by Eggenberger (1949) and used by Schlubach and Hoffmann-Walbeck (1949). Apples as a fruit have been investigated more thoroughly than other fruits (Hulme, 1955;Smock and Neubert, 1950 ;Wiley and Stembridge, 1961 ;and Woodmansee et al, 1959).…”
mentioning
confidence: 99%
“…Protopectin is the insoluble parent pectic compound of natural occurrence. In the ripening of fruits, the insoluble protopectin is changed gradually to soluble r 583 1 584 PECTIN METHYLESTERASE IN CANNED TOMATO FIRMNESS pectin by hydrolysis and depolymerization (Woodmansee and McClendon, 1959). Appleman and Conrad (1927) studied transformations in pectic substances during maturation and during canning.…”
Section: Mccollochmentioning
confidence: 99%
“…of fruits during normal development (Postlmayr et al, 1956;Woodmansee et al, 1959;Esau et al, 1962). It was found that fruit development is accompanied by an increase in water-soluble pectin substances and a decrease in protopectin content.…”
mentioning
confidence: 99%